Approaching community processes: The experience of building a relationship with the community of Barrio El Bosque in Guácimo, Limón - Jiménez Madrigal, María del Mar (2023)
Introduction: This process is framed in the experience of the Social Work students of the University of Costa Rica in the course TS0043 Workshop II Local organization and construction of citizenship II, who carried out a community process in the El Bosque community with the Asociación Administradora de los Acueductos y Alcantarillados Comunitarios (ASADA) Barrio El Bosque in the canton of Guácimo in the province of Limón. Main Objective: The objective of the project carried out was to reconstruct the community experience of connection with the participation processes, in order to make it useful for future approaches regarding the dynamics of the Barrio El Bosque community. Method: It could be possible through Participatory Action Research, which represents a series of techniques that start from the idea of integrating people to the process. Results: It was evident that one of the barriers to access to education is the poverty gap.  Also, the main activities are linked to the gender division of labor, which is why women invest a greater number of hours at work, when adding the days of domestic work.  The important spaces for the community are the plaza, being a meeting place; Furthermore, it is found that there is a high interest in water management;  However, there is a lack of knowledge of the processes related to water management in the communal aqueduct.